Economic vulnerability of timber resources to forest fires. - Rodríguez y Silva, Francisco; Molina, Juan Ramón; González-Cabán, Armando; Machuca, Miguel Ángel Herrera; y Silva, Francisco Rodríguez; Molina, Juan Ramón; González-Cabán, Armando; Machuca, Miguel Ángel Herrera (Journal of environmental management, 2012)
The temporal-spatial planning of activities for a territorial fire management program requires knowing the value of forest ecosystems. In this paper we extend to and apply the economic valuation principle to the concept of economic vulnerability and present a methodology for the economic valuation of the forest production ecosystems. The forest vulnerability is analyzed from criteria intrinsically associated to the forest characterization, and to the potential behavior of surface fires. Integrating a mapping process of fire potential and analytical valuation algorithms facilitates the implementation of fire prevention planning. The availability of cartography of economic vulnerability of the forest ecosystems is fundamental for budget optimization, and to help in the decision making process.
Keywords: Conservation of Natural Resources; Conservation of Natural Resources: economics; Decision Making; Economic valuation; Ecosystem; Fire economic losses; Fire prevention planning; Fires; Timber valuation; Trees

Recurrent fires and environment shape the vegetation in Quercus suber L. woodlands and maquis. - Schaffhauser, Alice; Curt, Thomas; Véla, Errol; Tatoni, Thierry (Comptes rendus biologies, 2012)
The effects of fire recurrence on vegetation patterns in Quercus suber L. and Erica-Cistus communities in Mediterranean fire-prone ecosystems of south-eastern France were examined on stands belonging to 5 fire classes, corresponding to different numbers of fires (from 0 to 4) and time intervals between fires since 1959. A common pool of species was identified among the plots, which was typical of both open and closed maquis. Fire recurrence reduced the abundance of trees and herbs, whereas it increased the abundance of small shrubs. Richness differed significantly between the most contrasting classes of fire recurrence, with maximal values found in control plots and minimal values in plots that had burned recurrently and recently. Equitability indices did not vary significantly, in contrast to Shannon's diversity index which mostly correlated with richness. Forest ecosystems that have burnt once or twice in the last 50 years were resilient; that is to say they recovered a biomass and composition similar to that of the pre-fire state. However, after more than 3-4 fires, shrubland communities displayed lower species richness and diversity indices than unburned plots. The time since the last fire and the number of fires were the most explanatory fire variables, governing the structure of post-fire plant communities. However, environmental factors, such as slope or exposure, also made a significant contribution. Higher rates of fire recurrence can affect the persistence or expansion of shrublands in the future, as observed in other Mediterranean areas.
The following values have no corresponding Zotero field: accession-num: 22721564
Keywords: Acidic soil; biomass; climate; cork-oak; Ecosystem; Erica arborea L.; Fire recurrence; Fires; France; Mediterranean Region; Plant communities; Plants; Plants: classification; Quercus; Seasons; Species Specificity; Trees

Vegetation history and human activity during the last 6000 years on the central Catalan coast (northeastern Iberian Peninsula) - Riera-Mora, S; Esteban-Amat, A (Vegetation History and Archaeobotany, 1994)
In this paper, we present the results of four pollen diagrams obtained from the northeastern coast of the Iberian Peninsula. These data, together with a set of 11 radiocarbon dates, allow us to make some suggestions about human activity in this area mainly during the last 6000 years. We have established four main stages of this activity. Phase I (7000-3000 B.P.) shows some sporadic human clearance without qualitative and/or quantitative changes inside the natural woodland, except for slight oscillations in AP values. These clearances are synchro- nous with Neolithic and Bronze Age settlements. Phase II (3000-1500/1300 B.P.) demonstrates a different hu- man action on the landscape along the Catalan coast. Sampling sites located in rich agricultural plains and close to urban centres show continuous woodland clear- ance during the Iberian period and especially during Ro- man times. In contrast, at boring sites far from these towns, the irregular and sporadic woodland disturbances continue, although these become more common. Phase III (1500/1300-850 B.P.) shows further woodland clear- ance fires along the coast. Pollen, archaeological and historical evidence allow us to relate this to the introduc- tion of grazing in the coastal area, connected with sea- sonal transhumance between the littoral and mountain regions. Phase IV (850-300/150 B.P.) is characterised by the final clearance of woodland and the development of olive farming. During this phase the agrarian Mediterra- nean landscape was definitively formed.
Keywords: Fires; Human disturbances; northeast Iberian Peninsula; olive; Seasonal transhumance